THE EFFECTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AS MEDIATOR ON ORGANIZATIONAL CULTURE AND CAREER DEVELOPMENT TO IMPROVE PERFORMANCE OF SATPOL PP AT DKI JAKARTA - Yana Mayiliana Sianipar; Singmin Johanes. Lo (Dinasti Publisher, 2020)
This study aims to analyze the Effect of Organizational Citizenship Behaviour as a mediator, Organizational Culture, and Career Development on employee performance. The object of this research is employees who work at the Satpol PP Province of DKI Jakarta . This research was conducted on 98 respondents from a total population of 5,119 employees. The sampling technique uses Simple Random Sampling technique. Determination of the number of samples for this study using the Slovin Formula and the sample used from the number of 130 questionnaire respondents collected 98 questionnaires mincludes 5 regions which are in the Province DKI Jakarta. This research method uses a quantitative descriptive approach using a questionnaire and data analysis used is SEM-PLS with SMART-PLS (Partial Least Square) analysis 3.2.7. The results of this study indicate that Organizational Citizenship Behaviour (OCB), Organizational Culture and Career Development have a significant positive effect on employee performance. The results showed the influence of the Organizational Culture variable (X1) had a significant positive effect on the Performance variable (Y). The effect of career development latent variables (X2) on Performance latent variables (Y) is significantly positive. The effect of the latent variable Organizational Citizenship Behaviour (OCB) (Z) has a significant positive effect on the latent variable of Performance (Y). Organizational Culture Variable (X1) significantly influences Performance (Y) and there is a significant positive effect on the Career Development latent variable (X2) of the Latent Variable Organizational Citizenship Behaviour (OCB) as a mediator (Z).